The Role of University Environment and Student Activities in Promoting Citizenship Values among Students of the University of Nizwa as Perceived by Its Students and Staff: A Field Study during the 2010–2011 Academic Semester - Al-Waheibi, Aisha Khalfan (Journal of Humanities & Social Sciences, 2025)
The current study aimed to highlight the role of the University Environment and student activities in promoting citizenship values among students at the University of Nizwa from first to fifth year, as well as to identify the differences between the responses of students and University staff. The study employed the descriptive-analytical method and developed a research instrument that was applied to a sample of 581 participants, including (481) students from both genders from the University of Nizwa and (100) staff members from both genders from the same university. The study reached to :The arithmetic means of the items measuring the role of the University Environment and student activities in promoting citizenship values among University of Nizwa students—as perceived by students and staff—ranged between (2.006 – 2.865), between the moderate to high range, and there are statistically significant differences at the significance level (α = 0.05) between the mean scores of student responses and staff responses at the University of Nizwa, with the differences favoring the staff. Also the study concluded recommendations and suggestions to distribute brochures once every semester that emphasize the importance of preserving the achievements of the nation, also assign Omani staff members who directly interact with students the responsibility of promoting citizenship values, using appropriate methods and timing, Educational institutions should organize student field trips to introduce them to the achievements of the national renaissance and the country, requiring them to write reports on these visits and rewarding those who excel in producing high-quality reports and should organize cultural seasons at least once a year to promote citizenship values.
Keywords: student activities; University Environment; development; citizenship values